Intellectual Property and Access to Medicines Patent Pooling as Access Enabler in Pharmaceutical Industry - Nemkyová, Renata; Štěrbová, Ludmila, 1957-; Müller, David, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The doctrine of intellectual property is based on the assumption that the exclusivity to commercialize a novel product granted to an inventor creates incentives to conduct research. In some areas, however, intellectual property can constitute a barrier to development of social welfare. In the area of access to medicines in developing countries, the intellectual property-related problem can take two forms. When needed products are not being developed and thus do not exist, lack of availability occurs. Lack of accessibility, on the other hand, arises when necessary medicines do exist, but their prices are prohibitive for people from resource-poor countries. Based on a detailed analysis of the patent and trade environment in the pharmaceutical sector, the thesis examines the potential of patent pooling as a joint intellectual property management strategy to increase access to medicines within the existing international intellectual property system. Particularly, it analyzes the effects of an existing pharmaceutical pool, the Medicines Patent Pool, on accessibility of antiretroviral medicines in low and middle income countries.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses